Eriocaulon idukkianum, a new tuberous species of Eriocaulaceae from southern Western Ghats, India - Manudev, K.m.; Robi, A.j.; Nampy, S. (Phytotaxa, 2017)
Eriocaulon idukkianum, a new species of Eriocaulaceae from the southern Western Ghats, India, is described and illustrated. The new species is remarkable by the presence of a rootstock with a terminal tuber and seeds without appendages. The closest relative of this species is probably E. tuberiferum, a taxon known from Kolhapur, Nashik and Satara districts of Maharashtra.